Ionization annealing of semiconductor crystals. Part two: the experiment - Garkavenko, A. S.; Mokritskii, V. A.; Banzak, O. V.; Zavadskii, V. A. (Technology and design in electronic equipment, 2014)
There is a conception that irradiation of semiconductor crystals with high energy electrons (300 keV) results in a significant and irreversible deterioration of their electrical, optical and structural properties. Semiconductors are typically irradiated by low voltage electron accelerators with a continuous flow, the current density in such accelerators is 10–5–10–6 A/cm2, the energy — 0,3–1 MeV. All changes in the properties after such irradiation are resistant at room temperature, and marked properties' recovery to baseline values is observed only after prolonged heating of the crystals to a high temperature. In contrast, the authors in their studies observe an improvement of the structural properties of semiconductor crystals (annealing of defects) under irradiation with powerful (high current) pulsed electron beams of high energy (E0 = 0,3–1 MeV, t = 0,1–10 ns, Ω = 1–10 Hz, j = 20–300 A/cm2). In their previous paper, the authors presented the theoretical basis of this effect. This article describes an experimental study on the influence of high-current pulsed electron beams on the optical homogeneity of semiconductor GaAs and CdS crystals, confirming the theory put forward earlier.